O desconcerto anarquista de John Cage - Simões, Gustavo Ferreira (2017)
In 1988, John Cage invented Anarchy, an experimental-writing book in which he praised the lives of anarchist women and men who had influence his anarchist ethicalaesthetical trajectory from mid-1940s to the 1990s. This influence was explicit until the last of his works, entitled “number pieces” (1987-1990), in which he presented what he called the “anarchical harmony”. During the 1940s, John Cage, by then an already famous artist after his “prepared piano”, started experiencing anarchism as a life practice in contact with artists and militants in the Black Mountain College and with The Living Theatre troupe in New York. In 1952, his piece 4’33” appeared as an anarchist-oriented direct action against the musical representations of sounds and in favour of the incorporation of noises excluded from the concert rooms. The following decades, living alongside artists and anarchists in the country side location of Stonypoint, Cage started publishing ‘how to improve the world (you only make matters worse), a diary kept from 1965 to 1982 in which he engaged with Henry David Thoreau’s writings, and antimilitary and ecological concerns. Although absent of almost all biographies and studies on Cage’s work, the artist experimented the anarchism in a fashion Edson Passetti calls “pathway heterotopies”. Beyond the book Anarchy and other explicit antiauthoritarian works, Cage lively experienced anarchy in the singular way he faced his existence, making out of the everyday life an invention in which he affirmed an otherwise path. According to Foucault, the cynical philosophers valued that notion to distinguish their scandalous lives from the other ones that reify regular values and conventions. This dissertation followed this path by establishing the reverberations between John Cage and the contemporary anarchist attitudes